Design of an educational program for secondary education based on the methodology " learning to do" in a competitive business - García Zapata, Teonila Doria (2016)
There is at present in Peru an important concern in the knowledge society to respond to the demands of the productive sector already that during these last decades the specialties in each college were introduced on the initiative of the teachers, without any study of the labor market or the needs of the different regions, nor of the contributions of the industrial engineers to secondary education directly or indirectly. Currently not enough to have manual skills, but a set of capabilities that graduates will enable them to solve problems and perform in different posts or create their own businesses. The current approach that gives the education for the job is not geared toward this.Throughout the development of the chapters you will find also the references on the requirements of the industry by people trained in certain skills and on the other hand will be able to appreciate the strong growth of youth labor list for work, thus leaving the great task of the State, the prioritize of the kind of education and that it is prospective and modern, to coordinate with the private entrepreneurial activity and that teachers are specialized in the different lines of technological knowledge current.